Soil nutrients and plant diversity affect ectomycorrhizal fungal community structure and functional traits across three subalpine coniferous forests - Yang, Nan; Hua, Jiani; Zhang, Jiangbao; Liu, Dong; Bhople, Parag; Li, Xiuxiu; Zhang, Yan; Ruan, Honghua; Xing, Wei; Mao, Lingfeng (Frontiers in Microbiology, 2022)
The symbiotic relationship between ectomycorrhizal fungi (EMF) and the roots of host plants is significantly important in regulating the health and stability of ecosystems, especially such as the climate warming affected subalpine forest ecosystems. Therefore, from the coniferous forest systems located in the Southern Qinghai-Tibetan Plateau, root tips from three forest tree species: Pinus wallichiana, Abies spectabilis and Picea spinulosa, were collected to look for the local causes of EMF community composition and diversity patterns. The EMF colonization rate, diversity and taxonomic community structure were determined by morphotyping and sanger sequencing of the fungal ITS gene from the root tip samples. Soil exploration types were identified based on the morphologies of the ectomycorrhizas, coupled with soil properties analysis and plant diversity survey. Contrasting patterns of EMF community and functional diversity were found across the studied three forests types dominated by different coniferous tree species. In terms of associations between soil and EMF properties, the total phosphorus (TP) and nitrate (NO3−) contents in soil negatively correlated with the colonization and Shannon diversity of EMF in contrast to the positive relationship between TP and EMF richness. The soil total nitrogen (TN), ammonium (NH4+) and plant diversity together caused 57.6% of the total variations in the EMF taxonomic community structure at the three investigated forest systems. Whereas based on the soil exploration types alone, NH4+ and TN explained 74.2% of variance in the EMF community structures. Overall, the findings of this study leverage our understanding of EMF dynamics and local influencing factors in coniferous forests dominated by different tree species within the subalpine climatic zone.